Zymosan-induced luminol-amplified chemiluminescence of whole blood phagocytes in experimental and human hyperthyroidism - Videla, Luis A.; Correa, Loreto; Rivera, Marcela; Sir, Teresa (Free radical biology & medicine, 1993)
Luminol-amplified CL of whole blood phagocytes was studied in rats given 3 consecutive doses of 0.1 mg L-triiodothyronine T 3/kg or in hyperthyroid patients, after stimulation by zymosan. In both cases, CL was significantly increased, in effect which was produced independently of the opsonization of the zymosan particles and markedly inhibited by azide. The in vitro addition of T 3 or L-thyroxine (T 4) to whole blood phagocytes from normal rats did not modify the opsonized zymosan-dependent CL, when assayed at the concentrations found in eutrhyroid subjects or in hyperthyroid patients. Administrations of propylthiouracil (400 mg/day for 2–3 months) to hyperthyroid patients reduced the CL response observed prior to treatment, to values comparable to those found in the euthyroid group. These data indicate that hyperthyroidism elicits an enhanced respiratory burst activity of whole blood phagocytes, probably related to adaptive changes induced by thyroid hormone on the mieloperoxidase-H 2O 2 system, rather than to direct actions of the hormone molecule or changes in the opsonic capacity of plasma.